PECULIARITIES OF TERRITORIAL DISTRIBUTION OF TICK-BORNE ENCEPHALITIS MORBIDITY WITHIN IRKUTSK RESIDENTS - O. V. Melnikova; E. A. Vershinin; V. M. Korzun; E. A. Sidorova; E. I. Andaev (Acta Biomedica Scientifica, 2012)
Irkutsk residents are infected, with, tick-borne encephalitis (TBE) mainly in Pribaykalie (Irkutsk region and Buryat Republic). TBE foci are rather various on this territory. Differences in some parameters of morbidity structure at the infection in different areas of this territory are reviewed, in this article.